InGaN/Cu2O Heterostructure Core-Shell Nanowire Photoanode for Efficient Solar Water Splitting - Zhao, Yingzhi; Xie, Lingyun; Chen, Hedong; Wang, Xingyu; Chen, Yongjie; Zhou, Guofu; Nötzel, Richard (Frontiers in Physics, 2021)
A novel n-InGaN/p-Cu2O NW photoanode exhibits 700% enhancement of the photocurrent compared to a bare InGaN NW photoanode for the oxygen evolution reaction in photoelectrochemical solar water splitting. The large photocurrent is due to maximized photocarrier separation and hole transfer to the surface in the depletion zone of the p-n heterojunction established by the p-Cu2O layer, forming a thin, uniform shell-layer around the n-InGaN NW core by electrodeposition. Thick Cu2O layers on top of the InGaN NWs act as common photocathodes for the hydrogen evolution reaction. The functional InGaN/Cu2O heterostructure core-shell NW photoanode is chemically self-stabilized at positive applied voltage by a thin CuO surface layer. Final deposition of the earth abundant NiOOH co-catalyst boosts the photocurrent of the InGaN/Cu2O/NiOOH complete NW photoanode into the competitive mA/cm2 range.